Research on scaling design and applicability evaluation of integral thermal-hydraulic test facilities: A review. (September 2019) - Deng, Chengcheng; Zhang, Xueyan; Yang, Ye; Yang, Jun
Highlights: Eleven major integral thermal-hydraulic test facilities are summarized in detail. Different scaling methodologies are compared and evaluated. The scaling distortion and evaluation applicability of integral test facilities are analyzed. Abstract: The integral thermal-hydraulic test facility is an important part of the design certification and safety review of nuclear power plants. During the past few decades, a considerable number of resources and efforts have been devoted to establishing integral test facilities and carrying out experimental programs throughout the world. These test facilities provide a large database for computer code assessments and a better understanding of thermal-hydraulic phenomena for postulated accident transients. In this paper, some main integral thermal-hydraulic test facilities are summarized from the perspective of scaling design and applicability evaluation. Scaling analysis methods are presented for the rational design of scaled-down test facilities. The main characteristics of these thermal-hydraulic test facilities are illustrated, including their construction history, scaling design, test matrix, verified codes and related research works. The scaling distortion and experimental applicability of different integral test facilities are compared and evaluated. This review is expected to provide the reference guidance for the rational design and application evaluation of integral thermal-hydraulic test facilities.